2018
DOI: 10.1016/j.dib.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of cellular gene targets of herpesvirus encoded microRNAs

Abstract: Herpesviruses have evolved to encode multiple microRNAs [viral miRNAs (v-miRs)], a unique feature of this family of double stranded DNA (dsDNA) viruses. However, functional role of these v-miRs in host-pathogen interaction remains poorly studied. In this data, we examined the impact of oral disease associated v-miRs viz., miR-H1 [encoded by herpes simplex virus 1 (HSV1)] and miR-K12-3 [encoded by Kaposi sarcoma-associated herpesvirus (KSHV)] by identifying putative targets of viral miRNAs. We used our publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In general, miRNAs and their direct target genes exhibit antagonistic expression patterns. We therefore selected all the downregulated genes from miR-H1 and miR-K12-3-3p datasets and scanned for potential v-miR binding sites [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, miRNAs and their direct target genes exhibit antagonistic expression patterns. We therefore selected all the downregulated genes from miR-H1 and miR-K12-3-3p datasets and scanned for potential v-miR binding sites [50].…”
Section: Resultsmentioning
confidence: 99%
“…These include cell replication, GPCR signaling, cell death, cell adhesion, etc. Moreover, employing in silico target prediction analysis, we identified hundreds of potential v-miR binding sites on the 3′UTRs of downregulated genes, even with stringent parameters [50; see Tables 1, 2 and supplementary data]. These genes are potentially regulated by v-miRs as our microarray data shows reduced mRNA levels and in silico analysis identifies single or in some cases, multiple v-miR binding sites suggesting that v-miR binding to host mRNA leads to transcript degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, similar to cellular miRNAs, viral miRNAs can also posttranscriptionally regulate numerous host genes. We recently showed that viral miRNAs can alter expression of both host mRNAs and miR-NAs in v-miR expressing oral keratinocytes and myeloid cells (macrophages) (Naqvi, Seal, Shango, Brambila, et al, 2018;Naqvi, Seal, Shango, Shukla, et al, 2018;Naqvi, Shango, Seal, Shukla, & Nares, 2018a). These widespread v-miR-mediated transcriptome changes can affect numerous cellular functions including immune responses, phagocytosis and cell migration.…”
Section: Studies From Various Groups Including Ours Have Demonstratedmentioning
confidence: 99%
“…To identify miR-142-3p gene targets with high confidence, we first selected downregulated genes. The 3′UTR of these genes were extracted using BioMart tool on Ensembl (http:// www.ensembl.org/biomart/martview/aa867419c3c6fd64f94af6d4a6549d3c) as previously described (31). Briefly, we selected Ensembl Genes 87 database and Human Genes dataset (GRCh38.p7).…”
Section: Mirna Target Prediction Of Differentially Downregulated Genesmentioning
confidence: 99%